A randomized controlled pilot study of the effectiveness of magnolia tea on alleviating depression in postnatal women. Issue 3 (10th February 2020) - Xue, Lili; Zhang, Jie; Shen, Huaxiang; Ai, Ling; Wu, Rongrong
Abstract: The magnolia tea has been used in traditional oriental medicine for multiple purposes including sleep aid. Postpartum depression is a mental illness that adversely affects the health and well‐being of many families with newborns. Given the known effectiveness and relative safety, herein we aimed to investigate whether magnolia tea has a palliative effect on postpartum depression. The qualified participants were randomly assigned to the intervention group or the control group. The participants in the intervention group drunk magnolia tea, while the control group received regular postpartum care only. The outcome variables including Postpartum Sleep Quality Scale (PSQS), Edinburgh Postnatal Depression Scale (EPDS), and Postpartum Fatigue Scale (PFS) were assessed and compared. In comparison with the control group, the intervention group demonstrated significant difference for physical‐symptom‐related sleep inefficiency (PSQS Factor 2) at 3 weeks post‐test ( t = −2.10, p = .03). The comparison results also revealed significant differences for PFS at both 3 weeks post‐test ( t = −2.02, p = .04) and 6 weeks post‐test ( t = −1.99, p = .04). Further, magnolia tea intervention significantly alleviated the symptoms of depression, reflected by the EPDS scores at 3 weeks post‐test ( t = −2.38, p = .02) and 6 weeks post‐test ( t = −2.13, p = .02). Our trial results suggested that drinking single‐ingredient magnolia tea for a 3‐week duration has positive effects on postpartum women. Magnolia tea is recommended as a supplementary approach to ameliorate sleep quality of postpartum women, while alleviating their symptoms of depression. Abstract : Our trial results suggested that drinking single‐ingredient magnolia tea for a 3‐week duration has positive effects on postpartum women. Magnolia tea is recommended as a supplementary approach to ameliorate sleep quality of postpartum women, while alleviating their symptoms of depression.